On-site measurements of the dynamic behaviour of Pelton turbines in the context of predictive maintenance. Issue 1 (1st September 2022) - Chiarelli, M; Hasmatuchi, V C; Amini, A; Decaix, J; Vetsch, D F; Boes, R M; Münch-Alligné, C
Abstract: The operating modes of pumped storage power plants, such as that of the Forces Motrices Hongrin-Léman (FMHL) in Switzerland, have drastically changed over the past decades due to the emergence of new renewable energies. The number of starts and stops experienced by machines increased significantly leading to broader fatigue cycles on the different parts of the machine. Therefore, the development of predictive maintenance tools is paramount to increase the availability and reinforce operational safety of the power plant. In this context, vibration measurements were performed on a 60 MW Pelton turbine of one of the ternary units of the FMHL power plant during dynamic and steady state operations. Non intrusive instrumentation has been deployed including accelerometers on the bearing. Comparing the ramp-up and ramp-down of the Pelton turbine, a hysteresis of the vibration level for a similar power has been observed. A reduction of the vibration levels when an additional injector is engaged during the ramp-up is observed. This reduction correlates strongly with the load reduction on the buckets when the total flow rate is distributed over more injectors, leading to a smaller flow rate per injector.